Dynamics of Star Cluster Formation: The Effects of Ongoing Star Formation and Stellar Feedback - Jeremy Karam; Michiko S. Fujii; Alison Sills (The Astrophysical Journal, 2025)
We perform a high-resolution zoomed-in simulation of star cluster assembly including the merger of two subclusters with initial conditions taken from previous large-scale giant molecular cloud (GMC) simulations. We couple hydrodynamics to N -body dynamics to simulate the individual stars themselves, and the gas-rich environment in which they evolve. We include prescriptions for star formation and stellar feedback and compare them directly to previous simulations of the same region without these prescriptions to determine their role in shaping the dynamics inherited from the cluster assembly process. The stellar mass of the cluster grows through star formation within the cluster and accretion of new stars and star-forming gas from a nearby filament. This growth results in an enhancement in the cluster’s rotation and anisotropic expansion compared to simulations without star formation. We also analyze the internal kinematics of the cluster once it has lost most of its gas and find that the rotational velocity and the velocity anisotropy profiles are qualitatively similar to those expected of clusters that have undergone violent relaxation. Additionally, rotation and anisotropic expansion are still present by the time of gas removal. This implies that evolution within the GMC was unable to completely erase the kinematics inherited by the merger.